Model Pembelajaran Index Card Match Untuk Meningkatkan Minat Belajar Al-Qur’an Hadist di Kelas VIII MTs Al-Ghozali Jatibarang Indramayu - Rusydi, Ibnu (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The factors underlying this research are that many students are not focused and less active during learning. Such as no motivation and interest that encourages learning, besides that, interest in learning is seen very little seen from. The purpose of the research using the Index Card Match learning model is to increase interest in learning the Qur'an and Hadith in class VIII students at MTs al-Ghozali. The method used by the researcher is classroom action research using descriptive observation. Based on the results obtained from this study, this learning model has an effect on increasing the interest in learning of students at MTs Al-Ghozali.